FLYWCH1, a novel transcription regulator with potential tumour suppressor activity - Almozyan, Sheema (2021)
Colorectal cancer (CRC) remains the world's third most deadly cancer. The molecular mechanisms underlying cancer development are multifactorial; however, hyperactivation of the Wnt pathway is the most common and primary molecular driver of this disease. Therefore, a better characterisation of the molecular mechanisms underlying the differences of Wnt/β-catenin signalling pathway action in normal versus cancer cells is warranted. Identifying specific protein(s) regulating Wnt/β-catenin differentially in healthy versus cancer cells are particularly of clinical interest.